Training needs on behavioural and psychological symptoms of dementia for professional caregivers in residential homes: a qualitative study - Pinazo, Carolina (Technium Social Sciences Journal, 2020)
The behavioural and psychological symptoms of dementia are very predominant in the disease, aggravating the suffering of people with dementia and increasing the physical and emotional burden professional caregivers are exposed to. Despite being so present in nursing homes, professional caregivers do not always have adequate training or the tools needed to deal with these situations. Objectives: to determine what knowledge professional caregivers in residential centres have about behavioural and psychological symptoms of dementia; to evaluate how behavioural and psychological symptoms associated with dementia are managed by professional caregivers in residential centres; and to know the training needs perceived by professional caregivers in behavioural and psychological symptoms of dementia. Professionals (in the fields of psychology, nursing coordination and geriatric assistance) from residential centres for the elderly were interviewed and a qualitative analysis of the interviews was carried out. The results show that most professionals do not know the behavioural and psychological symptoms of dementia or how to cope with them and have low levels of knowledge. This study highlights the need to design and provide ongoing training in the residential setting on the management of these symptoms.